Anti-cracking reinforcing material for coal mine

By using specific ratios of cement, dry sand, sodium fluoride, palm oil starch, castor oil modified isocyanate prepolymer and end-hydroxyl-based linear polyester polyurethane acetone in coal mine tunnel reinforcement materials, the problems of unadjustable initial settling time, short conveying distance and poor cracking resistance of the existing materials are solved, and the adjustable initial settling time, long-distance pumping and significantly enhanced cracking resistance of the materials are achieved.

CN119707383APending Publication Date: 2025-03-28鄂尔多斯市昊华红庆梁矿业有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311248907.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The initial settling time of existing coal mine tunnel reinforcement materials is unadjustable, the conveying distance is short, and the crack resistance is poor, making it difficult to meet the construction needs of coal mine tunnels.

Method used

A crack-resistant reinforcement material for coal mines, including cement, dry sand, sodium fluoride, palm oil starch, castor oil modified isocyanate prepolymer and end-hydroxyl-based linear polyester polyurethane acetone, is used to adjust the settling time and crack resistance of the material through specific preparation and stirring treatment.

Benefits of technology

It realizes adjustable initial settling time of the material, long-distance pumping and significantly enhanced crack resistance, meets the construction needs of coal mine tunnels, and ensures the stability and construction effect of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of special mortar, and particularly relates to an anti-cracking reinforcing material for a coal mine and a preparation method of the anti-cracking reinforcing material for the coal mine. Comprising the following steps: S1, raw material preparation: sequentially weighing the following raw materials in parts by weight: 350 to 450 parts of cement, 550 to 650 parts of dry sand, 0.9 to 3.6 parts of sodium fluoride, 3 to 6 parts of palm oil starch ester, 0.12 to 0.35 part of castor oil modified isocyanate prepolymer and 0.8 to 2 parts of hydroxyl-terminated linear polyester polyurethane acetone for later use; s2, preparation of a mixture I: adding the cement and the dry sand in the S1 into a stirrer for mixing treatment to obtain the mixture I; s3, preparing a mixture II; according to the invention, the setting time of the anti-crack reinforcing material can be adjusted, the pumping effect is improved, and the anti-crack effect of the reinforcing material can be greatly enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of special mortar, in particular to an anti-cracking reinforcement material for coal mines. Background Art

[0002] At present, the spray cementitious material used for the reinforcement of newly excavated coal mine tunnels in my country is generally concrete, which has the disadvantages of high rebound rate, difficulty in long-distance transportation, and easy water seepage during use. Therefore, in order to achieve good results, the reinforcement and sealing materials used for exposed surrounding rocks in coal mine tunnels must meet the following requirements: (1) The initial setting time can be adjusted to meet the engineering needs of different coal mine tunnels; (2) The material can ensure long-distance pumping, because the pulping equipment in the coal mine tunnel cannot be too close to the excavation equipment; (3) In order to meet the needs of ventilation and prevent gas accumulation in coal mine tunnels, the wind speed is generally not less than 0.15m / s, so the air circulation is fast and the moisture in the material evaporates quickly, resulting in a large number of cracks. Therefore, the anti-crack reinforcement material must meet good anti-crack performance.

[0003] The general method of increasing the anti-cracking effect of anti-cracking reinforcement materials is to add chemical fibers, wood fibers, etc., but in practice, it is found that the anti-cracking effect is not good after adding fibers in well-ventilated coal mine tunnels. After a large number of laboratory experiments, it was found that palm oil starch, castor oil modified isocyanate prepolymer, and terminal hydroxyl linear polyester polyurethane acetone can not only adjust the setting time of anti-cracking reinforcement materials and increase the pumping effect, but also greatly enhance the anti-cracking effect of anti-cracking reinforcement materials. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of the prior art anti-cracking reinforcement materials for coal mines, such as unadjustable initial setting time, short transportation distance and poor anti-cracking effect, and to propose an anti-cracking reinforcement material for coal mines.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] An anti-cracking reinforcement material for coal mines comprises the following raw materials in parts by weight: 350 to 450 parts of cement, 550 to 650 parts of dry sand, 0.9 to 3.6 parts of sodium fluoride, 3 to 6 parts of palm oil starch, 0.12 to 0.35 parts of castor oil modified isocyanate prepolymer and 0.8 to 2 parts of terminal hydroxyl linear polyester polyurethane acetone.

[0007] The present invention also proposes a method for preparing an anti-cracking reinforcement material for coal mines, comprising the following steps:

[0008] S1: Raw material preparation: weigh the following raw materials in parts by weight: 350-450 parts of cement, 550-650 parts of dry sand, 0.9-3.6 parts of sodium fluoride, 3-6 parts of palm oil starch, 0.12-0.35 parts of castor oil modified isocyanate prepolymer and 0.8-2 parts of hydroxyl-terminated linear polyester polyurethane acetone, and set aside;

[0009] S2: preparing mixture 1: adding cement and dry sand in S1 into a mixer for mixing to obtain mixture 1;

[0010] S3: preparing mixture 2: adding the sodium fluoride, palm oil starch, castor oil modified isocyanate prepolymer and terminal hydroxyl linear polyester polyurethane acetone in S1 into a mixer for mixing to obtain mixture 2;

[0011] S4: preparing a premix: adding the second mixture to the first mixture, and stirring the mixture with a stirrer to obtain a premix;

[0012] S5: preparing the anti-cracking reinforcement material: stirring the premix under a pressure of 0.9 MPa to obtain the anti-cracking reinforcement material.

[0013] Preferably, in S1, the cement is 42.5 grade ordinary Portland cement.

[0014] Preferably, in S1, the dry sand is dried river sand or machine-made sand with a fineness modulus of 2.5 to 3.

[0015] Preferably, in S2, the speed of the stirrer is set to 60-80 r / min and 90-110 r / min, the speed of 60-80 r / min corresponds to 7-10 min, and the speed of 90-110 r / min corresponds to 12-16 min.

[0016] Preferably, in S3, the internal temperature of the mixer is set to 30-50° C., and the mixing time is set to 30-40 min.

[0017] Preferably, in S4, the clockwise rotation speed of the mixer is set to 40-50 r / min, the clockwise rotation time is set to 5-8 min, the counterclockwise rotation speed of the mixer is set to 90-100 r / min, and the counterclockwise rotation time is set to 15-18 min.

[0018] Preferably, in S5, the internal temperature of the mixer is set to 50-60° C., and the mixing time is set to 15-20 min.

[0019] The present invention can be used to prepare anti-cracking reinforcement materials according to the construction conditions of different coal mine tunnels, and the on-site construction effect is good. The 3d uniaxial compressive strength of the present invention is 10MPa-40MPa, the 28d uniaxial compressive strength is 20MPa-60MPa, the 3d flexural strength is 5MPa-8MPa, the 28d flexural strength is stable at 10MPa-19MPa, the 3d impermeability pressure is 0.8MPa-1.5MPa, the 28d impermeability pressure is 1.5MPa-2.5MPa, and the initial setting time is 30min-90min. The material has high mechanical and impermeability properties in the early stage, and the later growth is significant. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0021] Embodiment 1

[0022] An anti-cracking reinforcement material for coal mines comprises the following raw materials in parts by weight: 450 parts of cement, 550 parts of dry sand, 1.8 parts of sodium fluoride, 6 parts of palm oil starch, 0.18 parts of castor oil modified isocyanate prepolymer and 0.8 parts of terminal hydroxyl linear polyester polyurethane acetone.

[0023] This embodiment also proposes a method for preparing an anti-cracking reinforcement material for coal mines, comprising the following steps:

[0024] S1: Raw material preparation: weigh the following raw materials in parts by weight: 450 parts of cement, 550 parts of dry sand, 1.8 parts of sodium fluoride, 6 parts of palm oil starch, 0.18 parts of castor oil modified isocyanate prepolymer and 0.8 parts of hydroxyl-terminated linear polyester polyurethane acetone, and set aside;

[0025] S2: preparing mixture 1: adding cement and dry sand in S1 into a mixer for mixing to obtain mixture 1;

[0026] S3: preparing mixture 2: adding the sodium fluoride, palm oil starch, castor oil modified isocyanate prepolymer and terminal hydroxyl linear polyester polyurethane acetone in S1 into a mixer for mixing to obtain mixture 2;

[0027] S4: preparing a premix: adding the second mixture to the first mixture, and stirring the mixture with a stirrer to obtain a premix;

[0028] S5: preparing the anti-cracking reinforcement material: stirring the premix under a pressure of 0.9 MPa to obtain the anti-cracking reinforcement material.

[0029] In this embodiment, in S1, the cement is 42.5 grade ordinary Portland cement, in S1, the dry sand is dried river sand or machine-made sand with a fineness modulus of 2.5, in S2, the speed of the mixer is set to 60r / min and 90r / min, the speed of 60r / min corresponds to 7min, and the speed of 90r / min corresponds to 12min, in S3, the internal temperature of the mixer is set to 30°C, and the mixing time is set to 30min, in S4, the clockwise rotation speed of the mixer is set to 40r / min, and the clockwise rotation time is set to 5min, the counterclockwise rotation speed of the mixer is set to 90r / min, and the counterclockwise rotation time is set to 15min, and in S5, the internal temperature of the mixer is set to 50°C, and the mixing time is set to 15min.

[0030] The mining depth of a coal mine is 1000m, the tunnel temperature is 28℃, the wind speed is 0.15m / s, and the distance from the slurry to the construction site after pumping is 70m. According to the mine pressure data and construction experience, the performance of the anti-cracking reinforcement material is specified: 3d uniaxial compressive strength ≧20MPa, 28d uniaxial compressive strength ≧50MPa, 3d flexural strength ≧5MPa, 28d flexural strength ≧15MPa, 3d anti-seepage pressure ≧1.0MPa, 28d anti-seepage pressure ≧2.0MPa, initial setting time 60min~80min.

[0031] After using the anti-cracking reinforcement material prepared in this embodiment, on-site monitoring shows that the properties of the anti-cracking reinforcement material are: 3d uniaxial compressive strength is 25MPa, 28d uniaxial compressive strength is 54MPa, 3d flexural strength is 7MPa, 28d flexural strength is 15MPa, 3d anti-seepage pressure is 1.0MPa, 28d anti-seepage pressure is 2.3MPa, and initial setting time is 100min; one year after the construction is completed, there is no cracking.

[0032] Embodiment 2

[0033] An anti-cracking reinforcement material for coal mines comprises the following raw materials in parts by weight: 350 parts of cement, 650 parts of dry sand, 1.9 parts of sodium fluoride, 3 parts of palm oil starch, 0.12 parts of castor oil modified isocyanate prepolymer and 2 parts of terminal hydroxyl linear polyester polyurethane acetone.

[0034] This embodiment also proposes a method for preparing an anti-cracking reinforcement material for coal mines, comprising the following steps:

[0035] S1: Raw material preparation: weigh the following raw materials in order by weight: 350 parts of cement, 650 parts of dry sand, 1.9 parts of sodium fluoride, 3 parts of palm oil starch, 0.12 parts of castor oil modified isocyanate prepolymer and 2 parts of hydroxyl-terminated linear polyester polyurethane acetone, and set aside;

[0036] S2: preparing mixture 1: adding cement and dry sand in S1 into a mixer for mixing to obtain mixture 1;

[0037] S3: preparing mixture 2: adding the sodium fluoride, palm oil starch, castor oil modified isocyanate prepolymer and terminal hydroxyl linear polyester polyurethane acetone in S1 into a mixer for mixing to obtain mixture 2;

[0038] S4: preparing a premix: adding the second mixture to the first mixture, and stirring the mixture with a stirrer to obtain a premix;

[0039] S5: preparing the anti-cracking reinforcement material: stirring the premix under a pressure of 0.9 MPa to obtain the anti-cracking reinforcement material.

[0040] In this embodiment, in S1, the cement is 42.5 grade ordinary Portland cement, in S1, the dry sand is dried river sand or machine-made sand with a fineness modulus of 2.8, in S2, the speed of the mixer is set to 70r / min and 100r / min, the speed of 70r / min corresponds to 9min, and the speed of 100r / min corresponds to 14min, in S3, the internal temperature of the mixer is set to 40°C, and the mixing time is set to 35min, in S4, the clockwise rotation speed of the mixer is set to 45r / min, and the clockwise rotation time is set to 7min, the counterclockwise rotation speed of the mixer is set to 95r / min, and the counterclockwise rotation time is set to 17min, and in S5, the internal temperature of the mixer is set to 55°C, and the mixing time is set to 18min.

[0041] The mining depth of a coal mine is 300m, the temperature of the tunnel is 19℃, the wind speed is 0.25m / s, and the distance from the slurry to the injection site is 30m. According to the calculated mine pressure and construction experience, the performance of the anti-cracking reinforcement material is specified: 3d uniaxial compressive strength is ≧15MPa, 28d uniaxial compressive strength is ≧25MPa, 3d flexural strength is ≧6MPa, 28d flexural strength and compressive strength are stable at ≧10MPa, 3d anti-seepage pressure is ≧0.9MPa, 28d anti-seepage pressure is ≧1.9MPa, and the initial setting time is 40min~60min.

[0042] After adopting the anti-cracking reinforcement material prepared by this embodiment, on-site monitoring obtained various properties of the anti-cracking reinforcement material: 3d uniaxial compressive strength is 20MPa, 28d uniaxial compressive strength is 33MPa, 3d flexural strength is 6MPa, 28d flexural strength and compressive strength are stable at 14MPa, 3d anti-seepage pressure is 0.9MPa, 28d anti-seepage pressure is 2.0MPa, and initial setting time is 45min; one year after the construction is completed, there is no cracking phenomenon.

[0043] Embodiment 3

[0044] An anti-cracking reinforcement material for coal mines comprises the following raw materials in parts by weight: 375 parts of cement, 625 parts of dry sand, 3.6 parts of sodium fluoride, 6 parts of palm oil starch, 2 parts of castor oil modified isocyanate prepolymer and 1 part of terminal hydroxyl linear polyester polyurethane acetone.

[0045] This embodiment also proposes a method for preparing an anti-cracking reinforcement material for coal mines, comprising the following steps:

[0046] S1: Raw material preparation: weigh the following raw materials in order by weight: 375 parts of cement, 625 parts of dry sand, 3.6 parts of sodium fluoride, 6 parts of palm oil starch, 2 parts of castor oil modified isocyanate prepolymer and 1 part of hydroxyl-terminated linear polyester polyurethane acetone, and set aside;

[0047] S2: preparing mixture 1: adding cement and dry sand in S1 into a mixer for mixing to obtain mixture 1;

[0048] S3: preparing mixture 2: adding the sodium fluoride, palm oil starch, castor oil modified isocyanate prepolymer and terminal hydroxyl linear polyester polyurethane acetone in S1 into a mixer for mixing to obtain mixture 2;

[0049] S4: preparing a premix: adding the second mixture to the first mixture, and stirring the mixture with a stirrer to obtain a premix;

[0050] S5: preparing the anti-cracking reinforcement material: stirring the premix under a pressure of 0.9 MPa to obtain the anti-cracking reinforcement material.

[0051] In this embodiment, in S1, the cement is 42.5 grade ordinary Portland cement, in S1, the dry sand is dried river sand or machine-made sand with a fineness modulus of 3, in S2, the speed of the mixer is set to 80r / min and 110r / min, the speed of 80r / min corresponds to a time of 10min, and the speed of 110r / min corresponds to a time of 16min, in S3, the internal temperature of the mixer is set to 50°C, and the mixing time is set to 40min, in S4, the clockwise rotation speed of the mixer is set to 50r / min, and the clockwise rotation time is set to 8min, the counterclockwise rotation speed of the mixer is set to 100r / min, and the counterclockwise rotation time is set to 18min, and in S5, the internal temperature of the mixer is set to 60°C, and the mixing time is set to 20min.

[0052] The mining depth of a coal mine is 100m, the temperature of the tunnel is 21℃, the wind speed is 0.35m / s, and the distance from the slurry to the injection site is 100m. According to the calculated mine pressure and construction experience, the performance of the anti-cracking reinforcement material is specified: 3d uniaxial compressive strength ≧10MPa, 28d uniaxial compressive strength is ≧20MPa, 3d flexural strength is ≧5MPa, 28d flexural strength compressive strength is stable at ≧10MPa, 3d anti-seepage pressure is ≧0.8MPa, 28d anti-seepage pressure is ≧1.5MPa, and the initial setting time is 50min~60min.

[0053] After adopting the anti-cracking reinforcement material prepared by this embodiment, on-site monitoring obtained the following properties of the anti-cracking reinforcement material: 3d uniaxial compressive strength is 12MPa, 28d uniaxial compressive strength is 23MPa, 3d flexural strength is 5MPa, 28d flexural strength and compressive strength are stable at 11MPa, 3d anti-seepage pressure is 0.9MPa, 28d anti-seepage pressure is 1.7MPa, and initial setting time is 55min; one year after the construction is completed, there is no cracking phenomenon.

[0054] According to Examples 1 to 3, it can be known that after a large number of laboratory experiments, it was found that palm oil starch, castor oil modified isocyanate prepolymer, and terminal hydroxyl linear polyester polyurethane acetone can not only adjust the setting time of the anti-cracking reinforcement material and increase the pumping effect, but also greatly enhance the anti-cracking effect of the anti-cracking reinforcement material.

[0055] The specific features, structures, materials or characteristics described in the present invention may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples and the features of the different embodiments or examples described in this specification without contradiction. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A crack-resistant reinforcement material for coal mines, characterized in that: The invention comprises the following raw materials in parts by weight: 350 to 450 parts of cement, 550 to 650 parts of dry sand, 0.9 to 3.6 parts of sodium fluoride, 3 to 6 parts of palm oil starch, 0.12 to 0.35 parts of castor oil modified isocyanate prepolymer and 0.8 to 2 parts of terminal hydroxyl linear polyester polyurethane acetone.

2. The method for preparing a crack-resistant reinforcement material for coal mines according to claim 1, characterized in that: The following steps are involved: S1: Raw material preparation: weigh the following raw materials in parts by weight: 350-450 parts of cement, 550-650 parts of dry sand, 0.9-3.6 parts of sodium fluoride, 3-6 parts of palm oil starch, 0.12-0.35 parts of castor oil modified isocyanate prepolymer and 0.8-2 parts of hydroxyl-terminated linear polyester polyurethane acetone, and set aside; S2: preparing mixture 1: adding cement and dry sand in S1 into a mixer for mixing to obtain mixture 1; S3: preparing mixture 2: adding the sodium fluoride, palm oil starch, castor oil modified isocyanate prepolymer and terminal hydroxyl linear polyester polyurethane acetone in S1 into a mixer for mixing to obtain mixture 2; S4: preparing a premix: adding the second mixture to the first mixture, and stirring the mixture with a stirrer to obtain a premix; S5: preparing the anti-cracking reinforcement material: stirring the premix under a pressure of 0.9 MPa to obtain the anti-cracking reinforcement material.

3. The method for preparing a crack-resistant reinforcement material for coal mines according to claim 2, characterized in that: In the S1, the cement is 42.5 grade ordinary Portland cement.

4. The method for preparing a crack-resistant reinforcement material for coal mines according to claim 2, characterized in that: In S1, the dry sand is dried river sand or machine-made sand with a fineness modulus of 2.5 to 3.

5. The method for preparing a crack-resistant reinforcement material for coal mines according to claim 2, characterized in that: In S2, the rotation speed of the mixer is set to 60-80 r / min and 90-110 r / min, the corresponding time of the rotation speed of 60-80 r / min is 7-10 min, and the corresponding time of the rotation speed of 90-110 r / min is 12-16 min.

6. The method for preparing a crack-resistant reinforcement material for coal mines according to claim 2, characterized in that: In S3, the internal temperature of the mixer is set to 30-50° C., and the mixing time is set to 30-40 min.

7. The method for preparing a crack-resistant reinforcement material for coal mines according to claim 2, characterized in that: In S4, the clockwise rotation speed of the mixer is set to 40-50 r / min, the clockwise rotation time is set to 5-8 min, the counterclockwise rotation speed of the mixer is set to 90-100 r / min, and the counterclockwise rotation time is set to 15-18 min.

8. The method for preparing a crack-resistant reinforcement material for coal mines according to claim 2, characterized in that: In S5, the internal temperature of the mixer is set to 50-60°C, and the mixing time is set to 15-20 minutes.